2012
DOI: 10.1179/crn.2012.033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for TMD with Occlusal Splint and Electromyographic Control: Application of the FARC Protocol in a Brazilian Population

Abstract: The purpose of this study was to apply Functional Anatomy Research Center (FARC) Protocol of TMD treatment, which includes the use of a specific type of mandibular occlusal splint, adjusted based on the electromyographic index, in a group of 15 patients with disc displacement, classified according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and then analyzing the results compared with the control group. The clinical evaluations were completed both before and after the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…The basic method of treatment is the use of occlusal splints made of hard material. These appliances are aimed at muscle relaxation and protection of teeth from further damage [7][8][9]. Some authors describe decreased muscle tone demonstrated in EMG in about 50% of patients with occlusal splints.…”
Section: Splintsmentioning
confidence: 99%
“…The basic method of treatment is the use of occlusal splints made of hard material. These appliances are aimed at muscle relaxation and protection of teeth from further damage [7][8][9]. Some authors describe decreased muscle tone demonstrated in EMG in about 50% of patients with occlusal splints.…”
Section: Splintsmentioning
confidence: 99%
“…W swoich badaniach Silva i wsp. (22) wykazali, że stosowanie szyn zgryzowych powoduje zwiększenie równowagi mięśniowej podczas ich stosowania oraz zmniejszenie nasilenia dolegliwości bólowych. Wyniki badań z zastosowaniem elektromiografii powierzchniowej sugerują również, że terapia szynami okludalnym powinna trwać minimum trzy miesiące, aby spowodować zmianę aktywności mięśni skroniowych przednich i żwaczy (23,14).…”
unclassified
“…Such hyperactivity causes muscle fatigue and spasms, thus generating more pain (3) . Several pain reduction techniques are used to treat TMD (4)(5)(6)(7)(8)(9)(10) . In physical therapy in particular, transcutaneous electric nerve stimulation (TENS) is one of the most utilized non-pharmacological analgesic resources (11) .…”
Section: Introductionmentioning
confidence: 99%